An observational pilot study of a novel loss of resistance syringe for locating the epidural space. (August 2021) - Athar, M.W.; Guo, N.; Ortner, C.; Carvalho, B.; Abir, G.; Riley, E.T.
Highlights: EpiFaith™ is a novel loss of resistance syringe for locating the epidural space. The EpiFaith™ signals when there is a loss of resistance. We report on the clinical use of the EpiFaith™ loss of resistance syringe. Three of four anesthesiologists rated it more highly than using their usual syringe. Abstract: Background: The EpiFaith® syringe is a novel loss-of-resistance syringe that utilizes a spring-loaded plunger that automatically moves forward within the syringe when there is a loss of resistance. We evaluated the syringe in a clinical setting among a cohort of pregnant women receiving neuraxial labor analgesia. Methods: In a non-randomized observational study, four anesthesiologists used the EpiFaith® syringe 10 times each while placing epidural catheters for labor analgesia. The anesthesiologists scored each placement on an 11-point Likert scale (−5 = absolutely worse, 0 = the same, and 5 = absolutely better than using their regular loss-of-resistance syringe technique). Results: All 40 neuraxial placements correctly located the epidural space. Air was used in the syringe in 35 of the 40 cases. In 50%, 27.5% and 22.5% of cases the anesthesiologists reported that using the EpiFaith® syringe was better than, the same as, or worse than using their regular syringe, respectively. There were no inadvertent dural punctures. Conclusions: This feasibility study found that three of the four anesthesiologists scored the EpiFaith® syringe as better or the same as using their regular loss-of-resistance syringe. More extensive studies are required to determine if the EpiFaith® syringe reduces adverse outcomes such as unintentional dural punctures.